The effect of drought and season on root life span in temperate arbuscular mycorrhizal and ectomycorrhizal tree species. (7th May 2019) - Liese, Rebecca; Leuschner, Christoph; Meier, Ina C.
Abstract: Fine roots play a key role in carbon (C) and nutrient cycling, since fine root life span drives soil organic C input and, thus, nitrogen (N) availability. The two main fungal symbioses found in temperate forest trees, ectomycorrhizae (ECM) and arbuscular mycorrhizae (AM), induce different root morphological changes upon infection, but the consequences for root life span are not clear. We explored differences in fine root life span between four AM and four ECM tree species using mini‐rhizotrons in a factorial drought experiment in large mesocosms. Median root life span of young AM and ECM trees differed fundamentally in its response to soil moisture and season of root birth; ECM root life span was reduced from 176 to 81 days in dry soil compared to moist soil, independent of season. By contrast, AM root life span was less responsive to drought, but decreased from 185 to 127 days when comparing roots produced early in the growing season versus mid‐season. In both mycorrhizal types, root life span was positively related to root diameter and negatively to the portion of lower order roots. Synthesis . While our results indicate morphological and architectural traits that predict root life span across tree species, they also indicate fundamental differences in the environmental response of root life span in young AM and ECM trees. This knowledge helps to improve global predictions of root life span. Abstract : Our results indicate fundamental differences in the environmental response of root life span in young AM and ECM trees. This knowledge helps to improve global predictions of root life span. Zusammenfassung: Feinwurzeln spielen eine Schlüsselrolle im Kohlenstoff (C)‐ und Nährstoffkreislauf, da die Lebensdauer der Feinwurzeln den organischen C‐Eintrag in den Boden und damit auch die Stickstoff (N)‐Verfügbarkeit beeinflusst. Die beiden wichtigsten Pilzsymbiosen, die bei temperaten Waldbäumen gefunden werden, die Ektomykorrhizen (ECM) und arbuskulären Mykorrhizen (AM), verursachen bei der Infektion verschiedene wurzelmorphologische Veränderungen, aber die Konsequenzen für die Wurzellebensdauer bleiben unklar. Wir haben Unterschiede in der Feinwurzellebensdauer zwischen vier AM‐ und vier ECM‐Baumarten mit Mini‐Rhizotronen in einem faktoriellen Trockenheitsexperiment in großen Mesokosmen untersucht. Die mittlere Wurzellebensdauer von jungen AM‐ und ECM‐Bäumen unterschied sich grundlegend in ihrer Reaktion auf die Bodenfeuchtigkeit und die Jahreszeit des Entstehens der Wurzel: Die ECM‐Wurzellebensdauer wurde in trockenen Böden im Vergleich zu feuchten Böden unabhängig von der Jahreszeit von 176 auf 81 Tage verringert. Im Gegensatz dazu reagierte die AM‐Wurzellebensdauer weniger auf Trockenheit, verringerte sich jedoch von 185 auf 127 Tage, wenn Wurzeln, die früh oder in der Mitte der Vegetationsperiode produziert wurden, miteinander verglichen wurden. In beiden Mykorrhizatypen stand die Wurzellebensdauer in einem positiven Verhältnis zum Wurzeldurchmesser und in einem negativen Verhältnis zum Anteil der Wurzeln niedrigerer Ordnung. Synthese . Während unsere Ergebnisse auf morphologische und architektonische Merkmale hinweisen, die die Wurzellebensdauer über verschiedene Baumarten hinweg vorhersagen, weisen sie auch auf grundlegende Unterschiede in der Umweltreaktion der Wurzellebensdauer in jungen AM‐ und ECM‐Bäumen hin. Dieses Wissen hilft, die globalen Vorhersagen der Lebensdauer von Wurzeln zu verbessern.